Trend of tobacco use: Reviewing the STEPS surveys conducted in Nepal - Mandal, Anil Kumar (Journal of Health Promotion, 2022)
The trend of tobacco use has changed over time in the world including Nepal. This study aimed to describe the trend of tobacco use in Nepal, is based on the review of the findings of three consecutive STEP wise approaches to non-communicable disease risk factor surveillance (STEPS) survey 2007, conducted by Society for Local Integrated Development Nepal (SOLID Nepal), and STEPS surveys 2013 and 2019, conducted by Nepal Health Research Council (NHRC). This study only compared the proportion of people who consumed tobacco during these surveys based on sex, age group, and age of initiation of tobacco use to describe the trend of tobacco use. The trend of any tobacco use, smoked tobacco use, and smokeless tobacco (SLT) use declined to 28.9% from 37.1%, to 17.1% from 26.2%, and to 18.3% from 18.6%, respectively during the period of 2007 to 2019. It shows that the prevalence of any tobacco use, smoked tobacco use and SLT use were in decreasing trend among men and women. In order to reduce it further, the government should conduct tobacco cessation programs considering SLT.